Diplomacy and the Modern Novel : France, Britain, and the Mission of Literature - Hepburn, William Allan; Daunais, Isabelle (Book collections on Project MUSE., 2020)
"Between 1900 and 1960, many writers in France and Britain either had parallel careers in diplomatic corps or frequented diplomatic circles: Paul Claudel, Albert Cohen, Lawrence Durrell, Graham Greene, John le Carre, Andre Malraux, Nancy Mitford, Marcel Proust, and others. What attracts writers to diplomacy, and what attracts diplomats to publishing their experiences in memoirs or novels? Like novelists, diplomats are in the habit of describing situations with an eye for atmosphere, personalities, and looming crises. Yet novels about diplomats, far from putting a solemn face on everything, often devolve into comedy if not outright farce. Anachronistic yet charming, diplomats take the long view of history and social transformation, which puts them out of step with their times--at least in fiction. In this collection of essays, eleven contributors reflect on diplomacy in French and British novels, with particular focus on temporality, style, comedy, characterization, and the professional liabilities attached to representing a state abroad. With archival examples as evidence, the essays in this volume indicate that modern fiction, especially fiction about diplomacy, is a response to the increasing speed of communication, the decline of imperial power, and the ceding of old ways of negotiating to new."--